The effects of language learning strategy (LLS) training on ESL college students’ strategies used / Nor Ashikin Ab Manan...[et. al.] - Ab Manan, Nor Ashikin; Alias, Ahmad Ashaari; Yusof, Johana; Pandian, Ambigapathy (Universiti Teknologi MARA Cawangan Pahang, 2011)
As a former colonial country, English was used as medium of instruction in Malaysian schools even after its independence in 1957 until the early 70‟s. At present, although Bahasa Malaysia is the official language and the medium of instruction in public schools as well as government agencies, English is considered as the second language and is still widely used at tertiary level as well as the business sectors. However, despite its prominence, English language proficiency among Malaysians has been in a steady state of decline. Studies conducted by Adnan (2000); Karib & Adnan (2005); Pandian (2007) reveal that Malaysians in general and students at secondary as well as tertiary levels in particular are not proficient in English. According to Nambiar (2007) a large number of Malaysian undergraduates find reading, interpreting and critically evaluating an academic text overwhelming especially when they have to express their understanding in a written or spoken form. Their knowledge of general as well as academic vocabulary is also poor (Osman and Bakar, 2009; Neo, 2009; Mokhtar, Rawian & Yahaya et al., 2010). These are among the most common complaints expressed by educators at tertiary level. These undergraduates also are very dependent on the lecturers and are not self-directed. It is noticed that the problems that they face are due to several factors including lack of appropriate learning strategies.